The safe disposal of hazardous wastes the special needs and problems of developing countries - Batstone, Roger 1940-; Smith, James E. 1941-; Wilson, David 1952- (World Bank e-Library., 1989)
This manual is intended for administrators and technical staff who have responsibilities for waste management, public health and environmental protection. This paper presents the classification of hazardous waste, its effects on health and the environment, the planning and implementation of programs in hazardous waste management, hazardous waste treatment, and disposal technologies, including economic and institutional considerations. The main emphasis of this manual is on the management aspects and on the technologies that may be appropriate for implementing a region-wide hazardous waste management program. Case studies from developing countries have been incorporated into the main text for the purpose of practical illustration. Sufficient information for at least a pre-feasibility assessment of various options for a hazardous waste management program is provided. A particularly useful section of this manual includes the examples of various operating systems for hazardous waste tracking and disposal, waste survey questionnaires and techniques, and landfill design and management practices.